Cognition and technology : co-existence, convergence, and co-evolution - Gorayska, Barbara; Mey, Jacob (J. Benjamins Pub., 2004)
This new collection of contributions to the field of Cognitive Technology (CT) provides the (to date) widest spectrum of the state of the art in the discipline -- a disciple dedicated to humane factors in tool design. The reader will find here a summary of past research as well as an overview of new areas for future investigations. The collection contains an extensive CT agenda identifying many as yet unsolved, CT-related, design issues. An exciting new development is the concept of 'natural technology'. Some examples of natural technologies are discussed and the merits of empirical investigati.